If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -14 = 2x + -5x + 10 Reorder the terms: -14 = 10 + 2x + -5x Combine like terms: 2x + -5x = -3x -14 = 10 + -3x Solving -14 = 10 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. -14 + 3x = 10 + -3x + 3x Combine like terms: -3x + 3x = 0 -14 + 3x = 10 + 0 -14 + 3x = 10 Add '14' to each side of the equation. -14 + 14 + 3x = 10 + 14 Combine like terms: -14 + 14 = 0 0 + 3x = 10 + 14 3x = 10 + 14 Combine like terms: 10 + 14 = 24 3x = 24 Divide each side by '3'. x = 8 Simplifying x = 8
| -3(b+2)=-3b-6 | | 4a-24=52 | | 7(x+3)+8=4x+3(-5+x) | | 4.12=16.81 | | -3(y-3y)+4=-4(3y-y)+6y+13y | | C=35-0.4C | | 3(x+4)=9x | | -3(b+2)=3b-6 | | -4-6x+7x=-16 | | 13-7x=11+5x | | 3x+4=9x | | 3x-15=-22 | | 9-x=3x-7 | | 8a+21+11=0 | | x^2+2x-248=0 | | 7x-3(5-x)=18 | | A+A=14-2 | | -16=a+71 | | 3.74=1.7b | | 8m-13=-4(2-2m) | | 7x+9-5x=-3 | | .75y=-.5 | | 3.74=17b | | 17(t-5)+4t=7(3t+3)-13 | | 6C+4C=9-2 | | 1=2x+17 | | -10(x+4)+46=-17-7 | | -5=-4m+5 | | -5=-4+5 | | -9+3x=0 | | s-29=-33 | | -3(5s-3)-9=-2(9s+6)-3 |